Managing Educational Stress and Coping with Conflicts among Undergraduate Students - Mehrad, Aida; Bouzedif, Meriem; Kodithuwakku, Thisaru Kavinda; Rweramila, Neema George; El Hajli, Saad; Cheraghsepehr, Mohammad (Pascasarjana UM, 2023)
Many higher-education students experience ongoing stress due to academic demands while studying at university or college. To examine the effects of educational stress on students' ability to learn, academic achievement, and mental health issues such as anxiety, sadness, sleep disturbances, and drug use problems, a qualitative research study was conducted using interview methods. The study explores the unique experiences of educational stress among undergraduate students, based on interviews with 14 students, and provides detailed insights into their stress levels. The research emphasizes the widespread impact of stress on students, including academic pressures and cultural adjustments, and focuses specifically on undergraduate students at the C3S business school. Addressing these stress factors is crucial for academic success and student well-being. Therefore, the study suggests implementing stress management and conflict resolution strategies, collaborating with counseling services, enhancing educational support services, and promoting mental health awareness through accurate strategies. The study also discusses its limitations and significance and offers future suggestions.